2018
DOI: 10.3390/s18010279
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Discriminant Analysis

Abstract: The Internet of Things (IoT) generates lots of high-dimensional sensor intelligent data. The processing of high-dimensional data (e.g., data visualization and data classification) is very difficult, so it requires excellent subspace learning algorithms to learn a latent subspace to preserve the intrinsic structure of the high-dimensional data, and abandon the least useful information in the subsequent processing. In this context, many subspace learning algorithms have been presented. However, in the process of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…S4 [55], and it is found that these methods are not as efficient as TS-LPP. Recently, several reports have suggested that two-step analysis for dimension reduction is useful, such as PCA-LPP, PCA-t-SNE, and PCA-UMAP [61][62][63][64]. Our results show that there is a useful case even if the same dimensionality reduction method is repeated in the two-step analysis, although the different algorithms are usually combined.…”
Section: A Structural Analysis Of Crystalline Liquid and Amorphous St...mentioning
confidence: 61%
“…S4 [55], and it is found that these methods are not as efficient as TS-LPP. Recently, several reports have suggested that two-step analysis for dimension reduction is useful, such as PCA-LPP, PCA-t-SNE, and PCA-UMAP [61][62][63][64]. Our results show that there is a useful case even if the same dimensionality reduction method is repeated in the two-step analysis, although the different algorithms are usually combined.…”
Section: A Structural Analysis Of Crystalline Liquid and Amorphous St...mentioning
confidence: 61%
“…S4, and it is found that these methods are not as efficient as TS-LPP. Recently, several reports have suggested that two-step analysis for dimension reduction is useful, such as PCA-LPP, PCA-t-SNE, and PCA-UMAP [58][59][60][61]. Our results show that there is a useful case even if the same dimensionality reduction method is repeated in the two-step analysis, although the different algorithms are usually combined.…”
Section: A Structural Analysis Of Crystalline Liquid and Amorphous St...mentioning
confidence: 61%
“…The network's availability and coverage area must allow for the use of networks to continue regardless of mobility, complex network topology changes, or changes in current technologies. All of this necessitates interoperability, handover, and recovery processes in the event of unattended operations [97].…”
Section: Availabilitymentioning
confidence: 99%